2016
DOI: 10.1177/0021998315617818
|View full text |Cite
|
Sign up to set email alerts
|

Solid particle erosion of composite materials: A critical review

Abstract: This article presents a critical review of papers dealing with solid particle erosion characteristics of polymer matrix composites, metal matrix composites, and ceramic matrix composites. In addition, the solid particle erosion characteristics of coatings for composite materials are also reviewed. Attention was paid to type of a reinforcement material (fiber/filler), amount of fiber/filler, fiber orientation, and interfacial strength between fiber/filler and matrix, which affect the solid particle erosion in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 194 publications
1
25
0
Order By: Relevance
“…Erosive wear occurs due to impact of high-velocity liquid or particles on solid surface. 24 Investigations into erosive behaviour of FRP materials have increased in recent years due to the fact that a wide variety of machinery components undergo erosion. For example, impact of dust particles on FRP gas turbine blades, impact of slurry on pump impeller blades, 25,26 etc.…”
Section: Tribological Performance Of Carbon and Glass Fibre-reinforcementioning
confidence: 99%
“…Erosive wear occurs due to impact of high-velocity liquid or particles on solid surface. 24 Investigations into erosive behaviour of FRP materials have increased in recent years due to the fact that a wide variety of machinery components undergo erosion. For example, impact of dust particles on FRP gas turbine blades, impact of slurry on pump impeller blades, 25,26 etc.…”
Section: Tribological Performance Of Carbon and Glass Fibre-reinforcementioning
confidence: 99%
“…Mathias et al [30] found that composite material was eroded easily than matrix polymer. Miyazaki [31] reviewed the papers of solid particle erosion and mentioned that the maximum erosion angle of composite material was larger than that of corresponding matrix. Ameli et al [32] reported that the addition of CF could improve the EMI shielding property of composites.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] However, the relatively low erosion resistance of polymers has been problematic, thus motivating researchers to seek effective solutions to improve it. [ 3,4 ] The use of hard and relatively brittle ceramic particles to reinforce polymeric composites is common in industry, mostly to enhance their mechanical properties such as elastic modulus and tensile strength. [ 5 ] However, in most cases, because of the relatively low fracture toughness of the ceramic particles, the erosion resistance of the resulting composite has been found to be lower than the polymer it was meant to reinforce.…”
Section: Introductionmentioning
confidence: 99%